Survey of software-defined networking data plane security - Zhongfu GUO; Xingming ZHANG; Bo ZHAO; Sunan WANG (网络与信息安全学报)
The software-defined network decouples the data plane from the control plane,aiming to introduce network innovation faster and fundamentally automate the management of large networks.Architecture innovation brings challenges and opportunities.Security issues limit the widespread adoption of software-defined networks.Attacks on the data plane may damage the entire software-defined network.The data plane structure and development trends were introduced,data plane security risks were analyzed,vulnerabilities were pointed out,and potential attack scenarios were identified.It also presents two specific solutions,discusses the significance and limitations,and looks forward to future security research directions.